Nannochloropsis sp. biomass recovery by Electro-Coagulation for biodiesel and pigment production - Matos, Cristina T. (2013)
Biofuel production from microalgal biomass could be an alternative solution to conventional biofuels typically dependent on food and high land/water demanding crops. However, the economic and energetic viability of microalgal biofuels is limited by their harvesting processes. The finding of innovative, low cost and efficient harvesting method(s) is imperative. In this study, the Electro-Coagulation (EC) was studied as a process to harvest the marine Nannochloropsis sp. microalga. Several EC operational conditions were studied and the best EC recovery efficiency (>97%) was achieved using a current density of 8.3 mA cm2 for 10 min. The quality of the recovered microalgal biomass was evaluated in terms of total lipids, fatty acid and pigment profile where no significant differences were observed after EC treatment. The energy requirements of the harvesting process were estimated and the combination of EC and centrifugation processes proved to decrease significantly the energy demand when compared with the individual process.